Pharmacokinetic optimization of antiretroviral therapy in pregnancy - Buckoreelall K. (2017)
Antiretroviral therapy suppresses replication of HIV allowing restoration and/or preservation of the immune system. Providing combination antiretroviral therapy during pregnancy can treat maternal HIV infection and/or reduce perinatal HIV transmission. However, providing treatment to pregnant women is challenging due to physiological changes that can alter antiretroviral pharmacokinetics. Suboptimal drug exposure can result in HIV RNA rebound, the selection of resistant virus or an increased risk of HIV-1 transmission to the infant. Increased drug exposure can produce unwarranted maternal adverse effects and/or fetal toxicity. Subsequently, dose adjustments may be necessary during pregnancy to achieve comparable antiretroviral exposure to non-pregnant adults. For several antiretrovirals, systemic exposure is decreased during the last trimester of pregnancy. By 6-12 weeks postpartum, concentrations return to those prior to pregnancy. Also, the extent of antiretroviral placental transfer to the fetus and degree of antiretroviral excretion into breast milk varies within, and between, antiretroviral drug classes. It is necessary to consider the pharmacological characteristics of each antiretroviral when optimizing combination therapy during pregnancy to treat maternal HIV infection and prevent perinatal HIV transmission. © 2012 Springer International Publishing Switzerland.